2019
DOI: 10.18805/lr-475
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary morphological characterization and evaluation of selected Bambara groundnut [Vigna subterranea (L.) Verdc.] genotypes for yield and yield related traits

Abstract: Forty nine (49) Bambara groundnut genotypes derived from single plant selection of diverse origin were evaluated for yield and yield components using 26 yield and yield related traits. Highly significant (P<0.001) differences were detected among the genotypes for canopy spread, petiole length, weight of biomass, seed weight and seed height, while seedling emergence, pod weight, seed length and seed width were significantly different (P<0.05). Principal component analysis identified nine influential components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
5
9
2
Order By: Relevance
“…Shegro et al [ 37 ] grouped the 20 Bambara groundnut accessions by PCA analysis based on quantitative traits. In our finding's variation percentages of PC1 and PC2 are 34.29% and 11.63% while [ 110 ] identified that PC1 and PC2 highly donated to the total variation at 19% and 14%, respectively, in Bambara groundnut. To cluster the genotypes into groups and subgroups, principal component scores were used because first a few principal components controlled all the information of the original variables [ 111 ].…”
Section: Discussioncontrasting
confidence: 42%
“…Shegro et al [ 37 ] grouped the 20 Bambara groundnut accessions by PCA analysis based on quantitative traits. In our finding's variation percentages of PC1 and PC2 are 34.29% and 11.63% while [ 110 ] identified that PC1 and PC2 highly donated to the total variation at 19% and 14%, respectively, in Bambara groundnut. To cluster the genotypes into groups and subgroups, principal component scores were used because first a few principal components controlled all the information of the original variables [ 111 ].…”
Section: Discussioncontrasting
confidence: 42%
“…In our findings first principal component (PC1) accounted more proportion of variation (45.88%) than PC2 (10.68%). Similar result was identified by Mohammed et al [84] of total variation at 19% (PC1) and 14% (PC2) in Bambara groundnut. The results of several researchers like Usman et al [35],…”
Section: Principal Component Analysissupporting
confidence: 90%
“…Similar results were reported by Khan et al (2021) of total variations at 45.88% (PC1) and 10.68% (PC2) in BGN. Several studies also support these findings (Farhad et al, 2008;Usman et al, 2014;Atoyebi et al, 2017a;Mohammed et al, 2020). In addition, PC1 is the most powerful criterion for selection for yield improvement (Adeoti et al, 2012).…”
Section: Discussionmentioning
confidence: 80%